COMPARACIÓN DEL ESFUERZO REPRODUCTOR EN DOS ESPECIES HERMANAS DEL GÉNERO SCELOPORUS (SAURIA: PHRYNOSOMATIDAE) CON DIFERENTE MODO REPRODUCTOR - Rodríguez Romero, Felipe; Méndez, Fausto R.; García Collazo, Rodolfo; Villagrán Santa Cruz, Maricela (Instituto de Ecología, A.C., 2002)
Relative clutch and litter mass were assessed in two sibling species (Sceloporus aeneus and S. bicanthalis) with different reproductive mode (oviparous and viviparous, respectively). S. bicanthalis had a greater relative litter mass than the relative clutch mass of S. aeneus, these values are the highest recorded for the genus Sceloporus. Individual neonate weights were not significantly different after hatching or birth, suggesting that differences in values of relative clutch and litter mass between species are due to different embryo stages.